2021
DOI: 10.3389/fcell.2021.667682
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent in vitro Maturation Efficacy of Human Oocytes – Is There an Optimal Age?

Abstract: In vitro maturation of oocytes from antral follicles seen during tissue harvesting is a fertility preservation technique with potential advantages over ovarian tissue cryopreservation (OTC), as mature frozen and later thawed oocyte used for fertilization poses decreased risk of malignant cells re-seeding, as compared to ovarian tissue implantation. We previously demonstrated that in vitro maturation (IVM) performed following OTC in fertility preservation patients, even in pre-menarche girls, yields a fair amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…This was confirmed by a second study where success rates hardly reached 15.5% in premenarchal compared to 28.2% in young postmenarchal patients [66]. Another very recent study demonstrated that in vitro maturation rates peaked at 38.3% between the ages of 18 and 24, but dropped dramatically in patients ≤5 or ≥30 years of age (4.6% and 8.9%, respectively) [62]. This approach represents an add-on method to potentially increase the fertility opportunities for cancer patients, especially in young women with cancer where transplantation of cortical tissue may pose a risk of relapse, but the in vitro maturation approach is currently too inefficient to be the only method used for fertility preservation [63].…”
Section: Immature Oocyte Collection During Ovarian Tissue Preparationmentioning
confidence: 63%
See 2 more Smart Citations
“…This was confirmed by a second study where success rates hardly reached 15.5% in premenarchal compared to 28.2% in young postmenarchal patients [66]. Another very recent study demonstrated that in vitro maturation rates peaked at 38.3% between the ages of 18 and 24, but dropped dramatically in patients ≤5 or ≥30 years of age (4.6% and 8.9%, respectively) [62]. This approach represents an add-on method to potentially increase the fertility opportunities for cancer patients, especially in young women with cancer where transplantation of cortical tissue may pose a risk of relapse, but the in vitro maturation approach is currently too inefficient to be the only method used for fertility preservation [63].…”
Section: Immature Oocyte Collection During Ovarian Tissue Preparationmentioning
confidence: 63%
“…OTC can be coupled with collection of immature oocytes at the time of freezing. Immature oocytes can be isolated by puncture from visible antral follicles on the surface of the ovary [61], retrieved from the medium used for ovary preparation [62] or collected from surplus ovarian medullary tissue [63]. The immature oocytes are then matured in vitro, fertilized or not, depending on the partner status of the patient, and subsequently vitrified.…”
Section: Immature Oocyte Collection During Ovarian Tissue Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-sectional study based on 58 women in an ICSI program also reported that the maturation rates of oocytes were significantly reduced in women over 30 years [ 133 ]. Similarly, a study based on 133 patients (aged 1–35 years) who underwent FP by ovarian tissue cryopreservation found that patients between menarche to 25 years could achieve the highest IVM rates, while women ≥30 years and pre-menarche girls (<6 years) obtained extremely low IVM rates (<10%) [ 134 ]. The changed oocyte maturation capacity in different ages may stem from the epigenetic changes [ 135 ] and differential gene expressions [ 136 , 137 ] of oocytes as they age.…”
Section: Woman’s Agementioning
confidence: 99%
“…However, previous studies have reported that maternal aging is associated with reduced IVM success rates and adverse events (8,9). IVM is an alternative option for ovarian tissue cryopreservation (OTC); however, the success rates for IVM can be very low when used to mature oocytes retrieved from females of advanced age during OTC (10). Therefore, there is an urgent need to identify the molecular mechanisms underlying IVM so that this technique can be become a driving force for the implementation of ART technology.…”
Section: Introductionmentioning
confidence: 99%